Oil and gas well cementing for engineers - Suleimanov, Baghir; Veliyev, Elchin F.; Aliyev, Azizagha A. (John Wiley & Sons, Inc., 2023)
"Oil and Gas Well Cementing for Engineers brings together the traditional technologies with new advancements in well cementing. The majority of the books dedicated to this topic are overloaded with technical information/data, therefore, they are not reader-friendly and prevents to set the whole picture. Students will benefit from the book as a primer, because it covers all the major aspects of cementing operations. Field specialists can make use of practical side of the book which contains the necessary calculations required on site. Also, laboratory evaluation of cement slurries is described in the book which will assist relevant specialists."--